2021
DOI: 10.1016/j.abb.2021.108923
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow in the sarcomere

Abstract: A highly organized and densely packed lattice of molecular machinery within the sarcomeres of muscle cells powers contraction. Although many of the proteins that drive contraction have been studied extensively, the mechanical impact of fluid shearing within the lattice of molecular machinery has received minimal attention. It was recently proposed that fluid flow augments substrate transport in the sarcomere, however, this analysis used analytical models of fluid flow in the molecular machinery that could not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The importance of viscous forces in synchronised and cooperative behaviour in this model is an interesting but not unexpected quality. The required values are greater than models for viscous drag within the sarcomere would suggest [51], however this aligns with the result found by Placais et al [9], who found the viscous friction coefficient required to obtain the expected coupling dynamics within their model was 2 to 3 orders of magnitude higher than predicted, whilst Julicher and Prost [17] used a damping coefficient assuming a viscosity 10 2 to 10 3 greater than water. The greater than expected restrictive force on filament movement is no longer generally thought to be caused just by the drag of negatively strained motors [28].…”
Section: Discussionsupporting
confidence: 82%
“…The importance of viscous forces in synchronised and cooperative behaviour in this model is an interesting but not unexpected quality. The required values are greater than models for viscous drag within the sarcomere would suggest [51], however this aligns with the result found by Placais et al [9], who found the viscous friction coefficient required to obtain the expected coupling dynamics within their model was 2 to 3 orders of magnitude higher than predicted, whilst Julicher and Prost [17] used a damping coefficient assuming a viscosity 10 2 to 10 3 greater than water. The greater than expected restrictive force on filament movement is no longer generally thought to be caused just by the drag of negatively strained motors [28].…”
Section: Discussionsupporting
confidence: 82%
“…However, if we assume that the internal energy dissipation in the thick filament-titin superstructure is minimal compared to the other sources of viscous energy dissipation (e.g., by filaments moving relative to their nearest neighbors), the force produced by the individual myosin motors during concentric muscle action will be directly related to the tension in the titin kinase domain. Furthermore, very recent work ( 71 ) suggests that viscous dissipation forces in the sarcomere are relatively minimal compared with active myosin force. Because of the inherent difficulty with any analysis of dissipative forces of this kind, we simply consider the microscopic TK tension to be directly proportional to the forces developed by the myosin motors attached to that filament.…”
Section: Resultsmentioning
confidence: 99%
“…The mean flow velocity through a slit-like pore of opening hav is proportional to the pore opening squared, hav2, and inversely proportional to haemolymph viscosity [58]. Therefore, the denser the muscle pack, the smaller the pore opening, and the stronger the pressure gradient needed to move haemolymph through the thorax [10]. And the greater the haemolymph viscosity, the greater the required pressure gradient.…”
Section: Discussionmentioning
confidence: 99%
“…To generate this pressure gradient, greater muscular action is demanded from the insect and, hence, greater metabolic energy is needed to do this mechanical work. For flying insects, viscosity is a major physiological parameter limiting flight performance by controlling the flow rate of fuel to the flight muscles, circulating nutrients and rapidly removing metabolic waste products [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%